Methadone and Metabolites in Hair of Methadone-Assisted Pregnant Women and Their Infants - Himes, Sarah K (2012)
Methadone is the recommended pharmacotherapy for opioid-dependent pregnant women. The primary aims of this study were to determine whether a dose-concentration relationship exists between cumulative maternal methadone dose, methadone and metabolite concentrations in maternal hair during pregnancy and whether maternal hair methadone and metabolite concentrations predict neonatal outcomes. MATERIALS AND METHODS: Hair specimens were collected monthly from opioid-dependent mothers enrolled in methadone treatment and 4 of their infants. Hair specimens were segmented (3cm), washed (maternal hair only) and analyzed for methadone, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) and 2-ethyl-5-methyl-3,3-diphenylpyrroline (EMDP) by liquid chromatography tandem mass spectrometry. RESULTS: There was large inter-subject variability and no dose-concentration relationship for cumulative methadone dose and methadone, EDDP, EMDP or total concentrations in hair. For individual women, a positive trend was noted for cumulative methadone dose and methadone and EDDP concentrations in hair. There was a positive linear trend for cumulative methadone dose and EDDP/methadone ratio in maternal hair, perhaps reflecting methadone’s induction of its own metabolism. Maternal methadone concentrations were higher than those in infant hair, and infant EDDP hair concentrations were higher than those in maternal hair. Maternal methadone dose, and methadone and EDDP hair concentrations were not correlated with peak infant neonatal abstinence syndrome (NAS) scores, days to peak NAS, duration of NAS, time to NAS onset, birth length, head circumference or amount of neonatal morphine pharmacotherapy. Maternal cumulative 3(rd) trimester methadone dose was positively correlated with infant birth weight. CONCLUSION: Methadone and EDDP in pregnant women’s hair are markers of methadone exposure and do not predict total methadone dose, nor neonatal outcomes from in utero methadone exposure.